Bentuk Makna dan Fungsi Falia bagi Ibu Hamil di Desa Loghia Kabupaten Muna - Salniwati Salniwati; Bilal Akbar Muhammad Arsad; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The phenomenon of the study of falia is important to investigate because it contains several values of local wisdom in a society, therefore the purpose of this research is to identify the form of falia for pregnant women and to describe the meaning and function of falia for pregnant women in Loghyia Village, Muna Regency. The method used is qualitative research method. The informants in the research consist of traditional leaders, community leaders, and traditional birth attendants (bhisa). The results of this research indicate that the oral tradition of falia for pregnant women is still maintained. The form of falia for pregnant women includes falia in the form of words or speech and falia in the form of actions. The meaning of falia for pregnant women is love, cultural and traditional social values, discipline, and health meanings. Meanwhile, the main function of falia is education, order, and behavior control